Prawattisāt, sātsanā, watthanatham, læ kānsưksā : rūam botkhwām Thaisưksā phư̄a ralưk thưng Sātsatrāčhān ʻIchiʻi Yōneʻo - Chatthip Nartsupha; Chalō̜ng Suntharāwānit ([Bangkok, Thailand] : Samnakphim Sāngsan, 2013)
Compilation of articles on Thai studies, including history, tradition and culture, and social conditions of Thailand; volume commemorating Ishii Yoneo, 1929-2010, a Japanese professor specializing in Southeast Asian history and Theravada Buddhism.
In Thai.
"石井米雄."
Includes bibliographical references.
Keywords: Ishii, Yoneo, -- 1929-2010; Thailand -- History; Thailand -- Social life and customs